Labor supply analysis with non-convex budget sets without the Hausman approach - John K. Dagsvik; Steinar Strøm (Statistics Norway, Research Department, 2017)
When the budget set is non-convex the application of the Hausman approach to estimate labor supply functions will in general be cumbersome because labor supply no longer depends solely on marginal criteria (first order conditions). In this paper we demonstrate that the conventional continuous labor supply model (including corner solution for non-participation) with non-convex budget sets in some cases can be estimated using only first order conditions provided the budget curve is continuously differentiable and the utility function belongs to a particular class. We subsequently discuss how the model can be specified econometrically. Finally, we discuss the application of the model to simulate the effect of counterfactual reforms.
Keywords: C51; J22; 330; Labor supply; non-convex budget sets; marginal criteria